فاتحة سورة الاسراء من منظور التحليل اللغوي دراسة في الاعجاز القرآني - خيشة، خولة; بن حامد، صبرينة; غضبان، صبرين; حدد، ماريا; عطاالله، هدى (University of Eloued جامعة الوادي, 2025)
ولإظهار الإعجاز القرآني في الآية فقد درسنا المستويات اللغوية التالية: أولا المستوى الصوتي، فقد تطرقنا إلى إحصاء الصوامت والصوائت ووضعنا لكل الأصوات مخارجها وصفاتها، وغاية هذا المستوى فهم أثر الأداء الصوتي في نقل المعاني والدلالة. ثانيا المستوى الصرفي، فقد درسنا الصيغ والأوزان لمفردات الآية المدروسة، ودلالة تلك الصيغ وكما درسنا الثنائيات التي تحتويها الآية وكان هدفنا إبراز الزيادات في الأفعال التي أضافت أثرا كبيرا في الآية. ثالثا المستوى النحوي، فقد تناولنا إعراب الكلمات وظاهرة التقديم والتأخير وهذا بين لنا دقة اختيار التراكيب وتعدد المعاني الممكنة. رابعا المستوى الدلالي والمعجمي، حيث ربطنا معاني الألفاظ بدلالاتها وبينا مقصد كل لفظة والغاية التي جاءت لأجلها على غيرها من الألفاظ الأخرى. خامسا المستوى النصي، فتناولنا فيه مظاهر الاتساق والانسجام والآليات الموجودة (الإحالة، الوصل، التكرار) بحيث ساعد التكرار على ربط الجمل وهو وسيلة فعالة للتذكير بما سبق. وكذلك مبدأ التغريض والذي بين لنا علاقة فاتحة السورة بباقي السورة، حيث أكدت الآية عظمة الله عز وجل وقدرته. To demonstrate the miraculous nature of the Quran in this verse, we studied the following linguistic levels: - First, the phonetic level. We addressed the enumeration of consonants and vowels, and identified the articulation points and characteristics of each sound. The goal of this level is to understand the impact of phonetic performance in conveying meanings and significance. -Second, the morphological level. We studied the forms and weights of the vocabulary in the verse under study, as well as the significance of those forms. We also studied the dual forms contained within the verse. Our goal was to highlight the additional verbs that added a significant impact to the verse. Third, the grammatical level. We addressed the inflection of words and the phenomenon of prioritization and postponement. This demonstrated the precision of the choice of structures and the multiplicity of possible meanings.Fourth: The semantic and lexical level, where we linked the meanings of words to their connotations and explained the purpose of each word and the purpose for which it was used, unlike other words.Fifth, the textual level, where we discussed the manifestations of coherence, harmony, and existing mechanisms (reference, connection, repetition). Repetition helps connect sentences and is an effective means of reminding us of what came before. We also discussed the principle of coherence, which demonstrated the relationship between the opening verse of the surah and the rest of the surah, as the verse affirms the greatness and power of God Almighty.
مذكرة ليسانس.لسانيات عامة.2025
Keywords: الإعجاز القرآني، المستوى الصوتي، الصيغ والأوزان، التقديم والتأخير، الاتساق والانسجام.; Quranic miracle; phonetic level; forms and meters; presentation and delay; consistency and harmony.